Phospholipase C-γ1 is involved in signaling the activation by high NaCl of the osmoprotective transcription factor TonEBP/OREBP - Irarrazabal, Carlos E. (National Academy of Sciences, 2009)
High NaCl elevates activity of the osmoprotective transcription factor TonEBP/OREBP by increasing its phosphorylation, transactivating activity, and localization to the nucleus. We investigated the possible role in this activation of phospholipase C-γ1 (PLC-γ1), which has a predicted binding site at TonEBP/OREBP-phospho-Y143. We find the following. (i) Activation of TonEBP/OREBP transcriptional activity by high NaCl is reduced in PLC-γ1 null cells and in HEK293 cells in which PLC-γ1 is knocked down by a specific siRNA. (ii) High NaCl increases phosphorylation of TonEBP/OREBP at Y143. (iii) Wild-type PLC-γ1 coimmunoprecipitates with wild-type TonEBP/OREBP but not TonEBP/OREBP-Y143A, and the coimmunoprecipitation is increased by high NaCl. (iv) PLC-γ1 is part of the protein complex that associates with TonEBP/OREBP at its DNA binding site. (v) Knockdown of PLC-γ1 or overexpression of a PLC-γ1-SH3 deletion mutant reduces high NaCl-dependent TonEBP/OREBP transactivating activity. (vi) Nuclear localization of PLC-γ1 is increased by high NaCl. (vii) High NaCl-induced nuclear localization of TonEBP/OREBP is reduced if cells lack PLC-γ1, if PLC-γ1 mutated in its SH2C domain is overexpressed, or if Y143 in TonEBP/OREBP is mutated to alanine. (viii) Expression of recombinant PLC-γ1 restores nuclear localization of wild-type TonEBP/OREBP in PLC-γ1 null cells but not of TonEBP/OREBP-Y143A. (ix) The PLC-γ1 phospholipase inhibitor U72133 inhibits nuclear localization of TonEBP/OREBP but not the increase of its transactivating activity. We conclude that, when NaCl is elevated, TonEBP/OREBP becomes phosphorylated at Y143, resulting in binding of PLC-γ1 to that site, which contributes to TonEBP/OREBP transcriptional activity, transactivating activity, and nuclear localization.